Проблемы развития банковского сектора России - Харитонова, О. В. (Культура народов Причерноморья, 2014)
В статье рассматриваются современные тенденции развития банковского сектора Российской Федерации, проведен анализ основных показателей уровня развития банковских организаций в динамике, дана оценка эффективности их работы. Аналитический материал статьи также содержит критический анализ современной денежно-кредитной политики, проводимой Центральным банком Российской Федерации для повышения безопасности банковских услуг и улучшения их качества. Выделены основные проблемы развития банковского сектора России на современном этапе развития, а также обоснованы основные пути их преодоления. У статті розглядаються сучасні тенденції розвитку банківського сектора Російської Федерації, проведено аналіз основних показників рівня розвитку банківських організацій в динаміці, дана оцінка ефективності їх роботи. Аналітичний матеріал статті також містить критичний аналіз сучасної грошово-кредитної політики, що проводиться Центральним банком Російської Федерації для підвищення безпеки банківських послуг та покращення їх якості. Виділено основні проблеми розвитку банківського сектора Росії на сучасному етапі розвитку, а також обґрунтовано основні шляхи їх подолання. The current trends in the banking sector of the Russian Federation based on analysis of the main indicators of the level of banking institutions’ development in the dynamics such as quantitative characteristics of credit institutions, macroeconomic indicators of the banking sector (the size and composition of the assets and liabilities of banks), the composition and structure of revenues and expenses of operating credit institutions are considered in the article. The evaluation of the sector’s efficiency is made. Analytical material article also contains a critical analysis of the current monetary policy pursued by the Central Bank of the Russian Federation to improve the security of banking services and improve their quality, namely: strengthening the requirements for credit institutions by the criterion of liquidity, control of rising interest rates on loans, improving the structure of the credit portfolio and other The main problems of the banking sector in Russia at the present stage of development. are allocated. The main areas to overcome them: improving the quality of bank financial management, including the implementation of the activities of mergers and acquisitions, an adequate combination of the mechanisms of protection and strengthening of supervision by the Bank of Russia are justified.